Efeitos do alongamento dos músculos flexores do quadril nos parâmetros de marcha em idosos - Almeida, Carlos Rafael de (2012)
The gait pattern is affected directly by human aging and the need for understanding of best practices for rehabilitation and prevention strategies to reduce the harmful effects in humans, contributing to the prevention of a serious public health problem that are falls in the elderly. The production on the subject developed in the first moment through a systematic review with meta-analysis on the effect of hip muscle stretching on gait parameters of the elderly and a chapter of the book about the muscle stretching and prevention of falls. The theoretical foundation of the chapter presents data that recommend the implementation of a programme of flexibility in the elderly with a view to reducing the deleterious effects of human aging, however in the systematic review show that there are sufficient scientific evidence for the recommendation of use of muscle stretching for hip flexors to improve gait speed of the elderly and to the other parameters there is no sufficient evidence. These results show a gap in relation to the application of a muscle-stretching program for the elderly due to the low number of studies found in the databases suggesting that new studies be developed with adequate methodological quality to produce scientific evidence that may assist in reducing the risk of falls in the elderly by contributing to prevention falls in this population